Anchoring and Upgrading Ultrafine NiPd on Room‐Temperature‐Synthesized Bifunctional NH2‐N‐rGO toward Low‐Cost and Highly Efficient Catalysts for Selective Formic Acid Dehydrogenation - Yan, Jun‐Min; Li, Si‐Jia; Yi, Sha‐Sha; Wulan, Ba‐Ri; Zheng, Wei‐Tao; Jiang, Qing (Advanced materials (Weinheim), 2018)
Hydrogen is widely considered to be a sustainable and clean energy alternative to the use of fossil fuels in the future. Its high hydrogen content, nontoxicity, and liquid state at room temperature make formic acid a promising hydrogen carrier. Designing highly efficient and low‐cost heterogeneous catalysts is a major challenge for realizing the practical application of formic acid in the fuel‐cell‐based hydrogen economy. Herein, a simple but effective and rapid strategy is proposed, which demonstrates the synthesis of NiPd bimetallic ultrafine particles (UPs) supported on NH2‐functionalized and N‐doped reduced graphene oxide (NH2‐N‐rGO) at room temperature. The introduction of the NH2N group to rGO is the key reason for the formation of the ultrafine and well‐dispersed Ni0.4Pd0.6 UPs (1.8 nm) with relatively large surface area and more active sites. Surprisingly, the as‐prepared low‐cost NiPd/NH2‐N‐rGO dsiplays excellent hydrophilicity, 100% H2 selectivity, 100% conversion, and remarkable catalytic activity (up to 954.3 mol H2 (mol catalyst)−1 h−1) for FA decomposition at room temperature even with no additive, which is much higher than that of the best catalysts so far reported. Ultrafine NiPd nanoparticles supported on a NH2‐functionalized and N‐doped reduced graphene oxide (NH2‐N‐rGO) substrate are successfully prepared through a facile one‐step strategy. The as‐prepared NiPd/NH2‐N‐rGO catalyst shows prominent catalytic performance (turnover frequency value up to 954.3 h−1), 100% H2 selectivity, and 100% conversion for formic acid dehydrogenation at 298 K without any additive.